Evaluation the Effect of Staining Agents on the Color Stability of Composite Resins that Polished at Different Interval Times (an in Vitro Study) - Shaymaa SH. Hassan (University of Mosul, College of Dentistry, 2016)
Aims: This study investigated the effect of polishing times (immediately, 1 hour and 24 hour after light curing) and staining solutions on the color stability of two composite resins. Materials and Methods: Nanocomposite (Filtek Z350) and microhybrid composite (Valux plus) were used. Sixty discs (8mm diameter×2mm height) were made for each composite, and divided into four groups: the first group was polished immediately after light curing; second group was polished after 1 h; third group was polished after 24 h of curing; and the fourth group was the control. Color was measured with spectrophotometer. After baseline color measurements, the specimens of each group divided into three subgroups; specimens of first subgroup were immersed in coffee; specimens of second subgroup were immersed in orange juice; specimens of third subgroup were immersed in distilled water, after 7 day of immersion, the color was measured again and ΔE were calculated. Statistical analysis: Two-way ANOVA, Duncan's Multiple Range test and t-test. Results: The influence of polishing times and staining solutions on color change was significant. Polishing 24 hours after curing presented lowest ΔE value. Coffee promoted more color change than orange juice and distilled water, Filtek Z350 showed lower ΔE than Valux plus. Conclusions: Immediate polishing negatively affect the color stability of composite resins, coffee had a significant influence on discoloration of composite resins. The nanocomposite showed higher color stability than microhybrid composite.